2022
DOI: 10.1038/s41419-022-04618-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface nucleolin is a novel ADAMTS5 receptor mediating endothelial cell apoptosis

Abstract: A Disintegrin and Metalloproteinase with ThromboSpondin motif (ADAMTS) 5 functions as an anti-angiogenic and anti-cancer protein independent of its metalloproteinase activity. Both full-length ADAMTS5 and TS5-p45, the autocatalytically cleaved C-terminal 45 kDa truncate of ADAMTS5, inhibits angiogenesis, and induces endothelial cell (EC) apoptosis. However, how ADAMTS5 triggers EC apoptosis remains unclear. This work shows that caspase-8 (Cas-8) and caspase-9 (Cas-9) are involved in TS5-p45-induced EC apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…In contrast, NCL protein contains an N-terminal, an RBD, and a C-GAR domain (Figure 5L). 40 Our results suggested that the RBD is sufficient for NCL to bind LIX1L (Figure 5M-R; Figure S4K-P). Furthermore, we confirmed the association between LIX1L-RBD and NCL-RBD and found that the association was blocked by RNase A (Figure 5S-U; Figure S4Q,R,U), indicating that RNA may mediate the association.…”
Section: Lix1l Interacts With Ncl Protein To Regulate Rrna Synthesis ...mentioning
confidence: 61%
“…In contrast, NCL protein contains an N-terminal, an RBD, and a C-GAR domain (Figure 5L). 40 Our results suggested that the RBD is sufficient for NCL to bind LIX1L (Figure 5M-R; Figure S4K-P). Furthermore, we confirmed the association between LIX1L-RBD and NCL-RBD and found that the association was blocked by RNase A (Figure 5S-U; Figure S4Q,R,U), indicating that RNA may mediate the association.…”
Section: Lix1l Interacts With Ncl Protein To Regulate Rrna Synthesis ...mentioning
confidence: 61%
“…In agreement with these studies, we found pro-cell survival role of LRP1 in human articular chondrocytes. Furthermore, several studies demonstrated cell survival and death functions for both previously reported and newly identified LRP1 ligands such as TIMP3 [50][51][52][53][54][55], ADAMTS5 [56], CTGF [57,58], CEMIP [59], SLIT2 [60,61], IGFBP7 [62][63][64] and HMGB2 [65]. The mechanisms by which LRP1 ligands regulate cell survival in chondrocytes remain unclear but the prolonged presence of one or several LRP1 ligands in the extracellular milieu may gradually alter cellular environment and metabolism leading to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…By binding with Fas ( 70 ), or with Ras via the C-terminal domain ( 71 ), NCL significantly promotes cancer cell proliferation and inhibits apoptosis by decreasing the expression of the pro-apoptotic BAX gene ( 72 ). Targeting cell-surface NCL might trigger multiple inhibitory effects, depending on the cell type ( 68 , 73 ). Taken together, to date, these observations highlight a critical role for NCL in tumorigenesis and tumor progression.…”
Section: Structure and Location Of Nucleolinmentioning
confidence: 99%